Problems and Prospects of Peace Tourism in Post-War Sri Lanka - Chandrasiri, Palliyaguruge Ravindra (E-Journal of Tourism; Volume 6 Number 1 (March 2019), 2019)
Peace tourism is becoming an emerging trend in the millennial era. It produces new dimensions of peace as well as tourism. Therefore, the concept of peace tourism is considered as a very broad concept with multiple aspects and there is no common agreed definition of peace tourism. The numerous facets of peace tourism are designed to lead “positive peace”, a term coined by Johan Galtung (1996). Post-war Sri Lanka is in a position of achieving positive peace through reconciliation. In this theoretical and empirical background, this paper is going to examine the problems and prospects of peace tourism in post-war Sri Lanka. What is peace tourism in the millennial era and how can it help achieve positive peace in Sri Lanka? These questions will be addressed in this paper while examining the relationship between peace tourism and reconciliation policies in post-war Sri Lanka. The research design of this study is based upon the Hermeneutic approach, apost-positivist research methodology. Other research methods of the study include key Informant Interview (KII) and content analysis methods. Key Words: Peace Tourism, Positive Peace, Post-war Sri Lanka, Reconciliation, Tourism in Millennial Era, Development.